A framework for institutional analysis for water resources management in a river basin context - Bandaragoda, Don Jayatissa (International Water Management Institute, 2000)
Presents a framework for institutional analysis, focusing on the three main pillars of institutions - laws, policies and administration. The report provides a brief set of guidelines, supported by an outline of some issues, constraints and prospects for institutional change.